Do microfinance institutions accomplish their mission? Evidence from the relationship between traditional financial sector development and microfinance institutions' outreach and performance - Vanroose, Annabel; D'Espallier, Bert (Applied economics, 2013)
This article analyses the relationship between outreach and performance of Microfinance Institutions (MFIs) on the one hand and traditional financial sector development on the other. The results indicate that MFIs reach more clients and are more profitable in countries where access to the traditional financial system is low. This finding is in line with the market-failure hypothesis: MFIs respond to a need that banks do not fulfill and MFIs flourish where the formal financial sector fails. Along the same line, the results demonstrate that MFIs serve poorer people in countries with well-developed financial systems. The results suggest that in countries with well-developed financial systems, the two sectors stand in more direct competition with each other. This competition pushes MFIs down the market and makes mission drift by MFIs less likely.